COMPARATIVE ANALYSIS THE COVERAGES OF FILARIASIS MASS PREVENTION DRUG (POPM) IN CENTRAL JAVA YEAR 2018: CASE STUDY IN GROBOGAN, SEMARANG, AND WONOSOBO - Setya Ningrum; Rokhmayanti Rokhmayanti; Mieng Nova Sutopo (Universitas Ahmad Dahlan, 2020)
Background: Filariasis is a disease caused by filarial worms and transmitted by mosquitoes that contain filarial worms. Pemberian Obat Pencegahan Masal (POPM) filariasis or Mass Prevention Drug is a program aimed to reduce the number of filariasis. The Survey of POPM in Grobogan, Semarang, and Wonosobo, shows there are different coverages of 65% and 85%. The purpose of this study is to compare the survey coverage of POPM filariasis. Seek the reason not to participate, and the characteristics of the respondents who did not take filariasis medicine in Grobogan, Semarang, and Wonosobo.Methods: Descriptive quantitative study was used in this study by collecting secondary data of POPM survey coverage in Grobogan, Semarang, and Wonosobo year 2018. Descriptive and comparative analysis was applied to respondent characteristics, filaria POPM coverage, and elaborate the unconformity to the filaria medication.Â Results: Grobogan coverage is low compared to Semarang and Wonosobo. The respondent said about traveling, don't know, and age as the reason to not take the filariasis medication.Conclusions: Among the three districts, Grobogan is the district with low filariasis medication coverage compared to Semarang and Wonosobo.Â